Atomistic simulations of mechanical response of a heterogeneous fcc/bcc nanolayered composite. (21st September 2022) - Xu, Kezhong; Zhai, Hua; He, Linghui; Ni, Yong; Lu, Pin; Wang, Gangfeng; Liu, Xuepeng
Abstract: Molecular dynamics simulations are performed to study the mechanical properties and deformation mechanisms of a heterogeneous face-centered cubic/ body-centered cubic Cu/Ta nanolayered composite under uniaxial tension and compression. The results show that the stress–strain curves exhibit two main yield points in tension while only one yield point during compression, and the deformation primarily experiences three stages. The first stage is linearly elastic at small strains, followed by the nucleation and propagation of dislocations and stacking faults in the Cu layers, and eventually the Ta layers yield to plastic deformation. The yield of the specimen is mainly determined by the dislocation evolution in the hard phase (i.e. Ta layers), which leads to a sharp drop in the stress–strain curve. We show that the heterogeneous nanolayered composite exhibits a good deformation compatibility during compression but an obvious deformation incompatibility between Cu and Ta layers in tension. The temperature effect is also systematically investigated. It is revealed that the yield of the specimen at higher temperature depends only on the dislocation evolution in the thick Ta layers, and the yield strengths in tension and compression both decrease with the increasing temperature. In particular, our computations show that high temperature can significantly suppress the dislocation activities in the Cu layers during deformation, which results in a lower dislocation density of the Cu layers compared with that of the Ta layers and thus causing an incompatible fashion among the constituent layers.